Legal Framework for Combating Crime in the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article presents the opinions of domestic and foreign scholars on the legal foundations of combating crime in the Republic of Uzbekistan. The Republic of Uzbekistan has established a comprehensive legal framework aimed at combating crime, ensuring public order, and protecting citizens' rights and freedoms. This framework encompasses constitutional provisions, criminal legislation, procedural laws, and specialized laws addressing specific types of crimes.